Inflammatory pseudotumor complicating metal-on-highly cross-linked polyethylene total hip arthroplasty. - Walsh, Alan J; Nikolaou, Vassilios S; Antoniou, John (J Arthroplasty, 2012)
Inflammatory masses or cysts occurring in the pelvis, thigh, and gluteal regions, often mimicking infection, occasionally arise after total hip arthroplasty procedures. Inflammatory pseudotumors comprise a subgroup of these lesions. Pseudotumors have been associated with pain, rashes, instability, neuropathy, and premature loosening of prosthetic components, often leading to early and difficult revision surgery. The association between such pseudotumors and metal-on-metal bearings has led to questions regarding the performance of these bearings in hip arthroplasty. We present a case of pseudotumor requiring revision surgery, which occurred uniquely around a metal-on-highly cross-linked polyethylene bearing.
Keywords: Aged; Arthroplasty, Replacement, Hip; Dermatitis, Contact; Granuloma, Plasma Cell; Hip Prosthesis; Humans; Male; Metals; Osteoarthritis, Hip; Polyethylene; Prosthesis Design; Reoperation; Treatment Outcome